Factors affecting employee performance in furniture manufacturing industry in Klang valley - Lai, Ying Ying (2019)
The purpose of this study is to examine the factors affecting employee performance in furniture manufacturing industry in Klang Valley which are worklife conflicts, leadership skills, work environment and motivations. A total of 250 set of questionnaire have been distributed to respondents. Statistical Packages for Social Science (SPSS) version 18.0 is used in order to statically measure and calculate the data and research findings. After the analysis, researchers found that all the variables are significant related to factors affecting employee performance in furniture manufacturing industry in Klang Valley. Among the independent variables, motivations have the strongest significant relationship with the dependent variable. The target population in the research study is manufacturing industry in Klang Valley. employees who work in furniture The limitations of this study which I had faced and the necessary recommendations are discussed towards the end of the chapter. The recommendations deliver effective suggestions and directions for further future studies.